The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1042/bj20060277
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of inositol biosynthesis through targeted mutagenesis in Dictyostelium discoideum: generation and characterization of inositol-auxotrophic mutants

Abstract: myo-Inositol and its downstream metabolites participate in diverse physiological processes. Nevertheless, considering their variety, it is likely that additional roles are yet to be uncovered. Biosynthesis of myo-inositol takes place via an evolutionarily conserved metabolic pathway and is strictly dependent on inositol-3-phosphate synthase (EC 5.5.1.4). Genetic manipulation of this enzyme will disrupt the cellular inositol supply. Two methods, based on gene deletion and antisense strategy, were used to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…Expression of the Dictyostelium ino1 gene [9], [26] was elevated both in dpoA null cells and cells treated with PO inhibitor (Figure 4A,B). Furthermore both conditions gave a 60-100% increase in expression of the genes encoding IMPase ( impA1 ), IPP ( ippA and ippB ) and Dd5P3, a phosphatase that converts I(1,4,5)P 3 to I(1,4)P 2 (see Table S1).…”
Section: Resultsmentioning
confidence: 95%
“…Expression of the Dictyostelium ino1 gene [9], [26] was elevated both in dpoA null cells and cells treated with PO inhibitor (Figure 4A,B). Furthermore both conditions gave a 60-100% increase in expression of the genes encoding IMPase ( impA1 ), IPP ( ippA and ippB ) and Dd5P3, a phosphatase that converts I(1,4,5)P 3 to I(1,4)P 2 (see Table S1).…”
Section: Resultsmentioning
confidence: 95%
“…The specifi city involves discrimination between substrates (substrate specifi city), similar parts of molecules and optical isomers (Fischbach et al ., 2006;Ju and Parales, 2006;Synowiecki and Woosowska, 2006). The mildness and specifi city of enzymes endow them with a high effi ciency for applications in fi ne-chemical/pharmaceutical synthesis, food processing, biosensor fabrication, biodegradation, biofuel cells, bioremediation and protein digestion in proteomic analysis (Polat et al ., 1997;Akgol and Dinckaya, 1999;Choudhary et al ., 2003;Hasan et al ., 2006).…”
Section: Applications As a Bioreactor: Immobilization Of Enzymesmentioning
confidence: 99%
“…Nevertheless, in vertebrates and lower eukaryotes, 2,3-BPG fulfills an essential role in glycolysis by priming the phosphoglycerate mutase reaction that converts 3-PG to 2-PG (4). More recently, experiments in Dictyostelium have suggested that 2,3-BPG, through an unknown mechanism, provides a molecular link between the turnover of phosphorylated inositol derivatives and glycolytic flux (5). Nonetheless, the most well studied function for 2,3-BPG is its regulation of whole-body oxygen homeostasis; 2,3-BPG executes this role because it is the main allosteric effector of hemoglobin in the majority of mammals.…”
mentioning
confidence: 99%
“…We considered this question to be intriguing because cellular levels of 2,3-BPG are only 1% of the total cellular content of InsP 6 (5,18), one of DdMipp1's alternate canonical substrates (15). The levels of 2,3-BPG in Dictyostelium have been estimated at Ϸ6 M (5), which is too low for our MDD-HPLC system to accurately resolve from other organic phosphates.…”
mentioning
confidence: 99%
See 1 more Smart Citation